Effect of Grain size of Porous Media on Physical Clogging - Rahim, Nawzad O.; Rasheed, Kamal A.; Qadir, Omed Saeed (Sulaimani Journal for Pure and Applied Sciences, 2007)
The effect of size of grains of porous media on physical clogging under constant flow rates was investigated experimentally. A sandy soil having particle size ranging from 355 to 1190 pm, fractioned into seven unisizes, was selected as the porous media" Two types of silt soils (smaller than 63 pm) were used as suspensions, Two concentrations (500 and 1000 mg/L) with three flow rates (116, 214 and 353 ml/min) were used. The results showed that, the permeability reduction (Kt/Ki) decreased with decreasing mean grain diameter (D50) of the porous media till a critical value of (D50/d50) after which a surface mat of suspension is formed on the surface of porous media. The effects of suspension type and flow rates on physical clogging seemed to depend on the pores size of the porous media.
Keywords: Bed Clogging; Permeability Reduction; Particle Infiltration; Plugging,Packed bed